The Principle of Separation of Powers and Its Relation to the Independence of the Parliamentary Deputy - Zighair Jabur, Dr. Abdul Kareem (Basra studies journal, 2024)
The independence of the parliamentary member is the basic pillar in the legislative and oversight process of parliamentary work, given the enormous tasks that the legislative authority has, despite the differences in political systems in determining these parliamentary powers and tasks. Since the legislative authority depends for its existence and performance of its duties on the human element related to its formation, represented by members of Parliament, Therefore, the performance of these tasks depends on the effectiveness of the members of Parliament and their role in performing their parliamentary duties, and this is directly related to the extent of the independence of the members of Parliament through what the constitutional and legal organization leaves behind the legislation of states in terms of dealing with the independence of members of Parliament and the extent of ensuring the provision of guarantees for this independence, especially since the nature of the member’s output The parliamentarian depends primarily on the work and activities he performs, whether inside or outside Parliament, with complete impartiality, objectivity and complete freedom. This independence is a necessity imposed by the reality of the situation as a result of the influences that the parliamentary member is exposed to, whether they come from the executive authority, individuals, as well as the judicial authority, and the source of these influences may be Parliament itself. In fact, the idea of the independence of the parliamentary member is not a relatively recent idea, but rather came as a result of long constitutional, political and jurisprudential developments that led to the necessity of adopting this principle. We find that the beginnings of the basis for this independence began with the idea of the emergence of the principle of separation of powers and the developments that accompanied it, which resulted in the independence of the legislative authority as an independent institution alongside the executive and judicial authorities. Hence the emergence of the principle of this independence as an urgent necessity imposed by the evolving political and constitutional reality.